Improving Simple Science Ability to Recognize Water Properties in Early Children - Fiqi Nurmanda Sari; Yusria Yusria; Huda Huda; Nurmalia Kasmadi; Athena Miranda Adrian (Universitas Islam Negeri (UIN) Sulthan Thaha Saifuddin Jambi, 2021)
This research aims to determine the level of success of children's scientific skills before and after being given action through experimental methods for children aged 5-6 years. This type of research is classroom action research (PTK) by having steps including preparation (RPPH), implementing actions, observing / observing, and also reflecting at each meeting. This research was conducted in two cycles. Each stage of the cycle includes planning, implementing, observing and reflecting. The subjects in this study consisted of 12 children including 5 girls and 7 boys. Data collection techniques used were observation, documentation, and interviews. The results of data analysis showed an increase in Pre-cycle, Cycle I, and Cycle II respectively as follows: no child succeeded in achieving the development of simple scientific skills in Pre-cycle 0 children (0%). Furthermore, there were 3 children (25%) who succeeded in achieving simple science development in Cycle I. And 9 children (75%) who succeeded in achieving simple science development in cycle II. From the description above it can be concluded that through the experimental method can improve the scientific skills of children aged 5-6 years.